No correlation between thrombin generation and emicizumab levels: implications for monitoring emicizumab therapy - Konrad van der Zwet; Mark Roest; Dana Huskens; Roger E.G. Schutgens; Lize F.D. van Vulpen; Kathelijn Fischer; Rolf T. Urbanus (Research and Practice in Thrombosis and Haemostasis)
Background: Emicizumab, a bispecific antibody that mimics factor (F)VIII, has significantly improved hemophilia A management. Although emicizumab levels can be measured, tools for estimating the hemostatic efficacy of emicizumab are lacking. Thrombin generation (TG) assays can distinguish bleeding phenotypes in persons with hemophilia A on FVIII prophylaxis and may also be used during emicizumab therapy. Objectives: To assess the association between TG parameters, emicizumab levels, and bleeding in patients on emicizumab therapy. Methods: A single-center longitudinal cohort study was conducted, with samples collected during the steady-state phase of emicizumab therapy. TG was measured using tissue factor (TF; TF-TG, 1 pM) and FXIa (FXIa-TG, 200 pM). Emicizumab concentrations were determined with mass spectrometry. Only treated bleeds were recorded. Pearson correlations (rho, r) were reported. Results: Eighty-five samples from 49 patients were analyzed during a median of 1 year of emicizumab therapy. Most bleeds were traumatic (97%; n = 30), whereas 1 bleed was spontaneous. At 12 months, TF-TG (r = 0.42) showed a borderline correlation, and FXIa-TG (r = 0.15) showed no correlation with emicizumab concentrations. Although FXIa-TG showed a 9% higher endogenous thrombin potential in patients with zero vs ≥1 treated bleed (endogenous thrombin potential: 957 vs 878 nM/min, P = .045), neither the FXIa-peak height nor TF-TG showed any association with traumatic bleeding. Conclusion: TG parameters showed no clinically relevant correlations with emicizumab plasma concentrations, were not associated with traumatic bleeding, and showed considerable intrapatient variability. Therefore, TG was not considered useful for monitoring coagulation potential in patients on steady-state emicizumab prophylaxis.